The impact of synoptic storm likelihood on European subseasonal forecast uncertainty and their modulation by the stratosphere - Rupp, Philip; Spaeth, Jonas; Afargan-Gerstman, Hilla; Büeler, Dominik; Sprenger, Michael; Birner, Thomas (Copernicus Publications, 2024)
Weather forecasts at subseasonal-to-seasonal (S2S) timescales have little or no forecast skill in the troposphere: individual ensemble members are uncorrelated and span a range of atmospheric evolutions that are possible for the given set of external forcings. The uncertainty of such a probabilistic forecast is then determined by this range of possible evolutions – often quantified in terms of ensemble spread. Various dynamical processes can affect the ensemble spread within a given region, including extreme events simulated in individual members. For surface pressure or geopotential height forecasts over Europe, such extremes are mainly comprised of synoptic storms propagating along the North Atlantic storm track. We use ECMWF re-forecasts from the S2S database to investigate the connection between different storm characteristics and ensemble spread in more detail. We find that the presence of storms in individual ensemble members at S2S time scales contributes about 20 % to the total geopotential height forecast uncertainty over Northern Europe. Furthermore, certain atmospheric conditions associated with substantial anomalies in the North Atlantic storm track show reduced geopotential height ensemble spread over Northern Europe. For example, during periods with a weak stratospheric polar vortex, the genesis frequency of Euro-Atlantic storms is reduced and their tracks move equatorwards. As a result, we find weaker storm magnitudes and lower storm counts, and hence anomalously low subseasonal ensemble spread, over Northern Europe.